Mitochondrial complex II has a key role in mitochondrial-derived reactive oxygen species influence on plant stress gene regulation and defense - Gleason, C.; Huang, S.; Thatcher, L.; Foley, R.; Anderson, C.; Carroll, A.; Millar, A.; Singh, Karambir (National Academy of Sciences, 2011)
Mitochondria are both a source of ATP and a site of reactive oxygen species (ROS) production.However, there is little information on the sites of mitochondrial ROS (mROS) production or the biological role of such mROS in plants. We provide genetic proof that mitochondrial complex II (Complex II) of the electron transport chain contributes to localized mROS that regulates plant stress and defense responses. We identify an Arabidopsis mutant in the Complex II subunit, SDH1-1, through a screen for mutants lacking GSTF8 gene expression in response to salicylic acid (SA). GSTF8 is an early stress-responsive gene whose transcription is induced by biotic and abiotic stresses, and its expression is commonly used as a marker of early stress and defense responses. Transcriptional analysis of this mutant, disrupted in stress responses 1 (dsr1), showed that it had altered SA-mediated gene expression for specific downstream stress and defense genes, and it exhibited increased susceptibility to specific fungal and bacterial pathogens. The dsr1 mutant also showed significantly reduced succinate dehydrogenase activity. Using in vivo fluorescence assays, we demonstrated that root cell ROS production occurred primarily from mitochondria and was lower in the mutant in response to SA. In addition, leaf ROS production was lower in the mutant after avirulent bacterial infection. This mutation, in a conserved region of SDH1-1, is a unique plant mitochondrial mutant that exhibits phenotypes associated with lowered mROS production. It provides critical insights into Complex II function with implications for understanding Complex II's role in mitochondrial diseases across eukaryotes.